Desarrollo De indicadores de sostenibilidad ambiental en la Laguna de Yambo, Cantón Salcedo, Provincia de Cotopaxi. - Caguana Achachi, Luis Fernando (2022)
This research study is based on the development and selection of environmental sustainability indicators. The study is based on the characterization of the area and an environmental approach that allows contextualizing the variables in relation to human activities in an ecosystem in constant degradation. For this, it was important to consider the practices that are carried out for the control and development of the natural environment of the area. Thus, under the ordinance of the Municipality GAD of Salcedo that is developed for the welfare of the conservation of the Yambo Lagoon under considerations of the obligations for visitors and users and in the context of the United Nations Commission on Sustainable Development, which was created in 1992 contemplates the inclusion of an economic, social, environmental and institutional dimension allowing as a result to develop indicators that based on data collection, structure a referential base for the validation of the variables that in close relation to the SDG, make it possible to respond to the problems that are generated or could be generated within the area of study forming a tool for the conservation, use, and socio-environmental use. Therefore, when dealing with human activities in agriculture, tourism, employment, infrastructure, housing, health, among others, and in the environmental aspect, water, soil, biodiversity, etc., the variables within the same population based on the territory of Panzaleo parish are contemplated which under INEC 2010 sources contemplates a total of 3,455 inhabitants and a representation of a 45.90% of men and 54.10% of women, allowing a degree of acceptance of more than 85% in the framework of the development of indicators for decision-making that under environmental criteria and social participation allows for socio-economic environmental equity.